Effect of temperature and growth time on vertically aligned ZnO nanorods by simplified hydrothermal technique for photoelectrochemical cells - Mohd Fudzi, Laimy; Zainal, Zulkarnain; Lim, Hong Ngee; Chang, Sook Keng; Holi, Araa Mebdir; Sarif @ Mohd Ali, Mahanim (MDPI, 2018)
Despite its large band gap, ZnO has wide applicability in many fields ranging from gas sensors to solar cells. ZnO was chosen over other materials because of its large exciton binding energy (60 meV) and its stability to high-energy radiation. In this study, ZnO nanorods were deposited on ITO glass via a simple dip coating followed by a hydrothermal growth. The morphological, structural and compositional characteristics of the prepared films were analyzed using X-ray diffractometry (XRD), field emission scanning electron microscopy (FESEM), and ultraviolet-visible spectroscopy (UV-Vis). Photoelectrochemical conversion efficiencies were evaluated via photocurrent measurements under calibrated halogen lamp illumination. Thin film prepared at 120 °C for 4 h of hydrothermal treatment possessed a hexagonal wurtzite structure with the crystallite size of 19.2 nm. The average diameter of the ZnO nanorods was 37.7 nm and the thickness was found to be 2680.2 nm. According to FESEM images, as the hydrothermal growth temperature increases, the nanorod diameter become smaller. Moreover, the thickness of the nanorods increase with the growth time. Therefore, the sample prepared at 120 °C for 4 h displayed an impressive photoresponse by achieving high current density of 0.1944 mA/cm2.